IoT supported smart home for the elderly - Sokullu, Radosveta İvanova; Akkaş, Mustafa Alper; Demir, Eren (Elsevier B.V., 2020)
Continuously progressing technology helps improve human living standards and make human life easier. A large portion of these developments is targeting the healthcare sector and especially in the last decade has been focused on helping elderly patients extend their independent existence in their preferred environments. In this article, we present a smart home IoT based system for elderly people and people with partial memory loss (MCI patients, dementia patients etc) which ensures their safety and provides early warnings to help them overcome small everyday problems typical for such disorders. Data is continuously collected from various ambient sensors and is used for the contextual detection of their activities. Unobtrusively monitoring the patient's behaviour in his/her home is assured as well as providing necessary data to relatives and/or caregivers. An emergency wristband is added to deal with extraordinary and dangerous situations like unexpected fall, gas/water left open in the house, etc. The developed prototype is a low-cost solution, under 100 USD, in which low energy consumption and ease of integration help greatly increase its applicability.
Keywords: Dementia; Internet of Things; Smart home; Wireless patient monitoring system